대체제설제인 EFD-1과 PC-10의 밀, 보리, 시금치 생육에 미치는 영향 - 이대원; Dae Weon Lee (Hanguk hwangyeong nonghak hoeji, 2015)
동절기에 폭설 등의 기상변화로 인해 제설제의 사용이 증가하고 있고, 교통사고의 예방과 인적 손실을 최소화하기 위해 이용된다. 제설제의 주성분으로는 염화칼슘과 염화나트륨이 있다. 최근에 수질오염, 농업생산성 감소 등의 염화물계 제설제의 부작용을 저감하기 위해 대체 제설제에 대한 관심이 높아지고 있다. 본 연구는 밀, 보리, 시금치에 대해 PC-10과 EFD-1 제설제의 영향을 조사하였다. PC-10과 EFD-1제설제를 사용하여 보리, 밀, 시금치의 성장과 발아, 생체량을 조사하였다. EFD-1은 조사작물에 대해 PC-10 보다 발아억제가 더 강하였다. 제설제 영향에 대한 관능조사에서 시금치는 다른 작물에 비해 크게 영향을 받지 않았다. 토양 내 제설제 잔류조건에서 EFD-1은 PC-10에 비해 발아억제효과가 높았다. 조사작물의 줄기 및 뿌리 생장은 EFD-1처리구보다PC-10 처리구가 대조구와 비교하였을 때 상대적으로 양호하였다. 제설제의 처리구는 생체량 측정에서 조사작물 모두에서 대조구에 비해 낮았으며, 2% 이상의 처리농도에서 PC-10은 23-35%, EFD-1은 39-84%의 생체량 감소를 보였다. 이상의 결과들은 대체제설제인 PC-10이 EFD-1 비해 조사작물들의 발아, 생장, 생체량 감소에 영향을 덜 주는 것으로 판단된다. BACKGROUND: During the winter, the use of deicers was rapidly increased for reduction of traffic accidents as well as injuries in Korea, whose components are largely comprised of calcium chloride and sodium chloride. Recently, to reduce the adverse effects of chloride-deciers such as pollution of water and soil, and decrease of agricultural productivity, the attention of eco-friendly deciers have been increased. This study aimed to investigate biological effects of magnesium chloride deicer (PC-10) and organic acid deicer (EFD-1) against wheat, barley, and spinach. METHODS AND RESULTS: We examined the effect of two deciers, PC-10 and EFD-1 on the seed germination and growth of wheat, barley and spinach. EFD-1 showed higher suppression of the germination than PC-10 among tested crop seeds. In demage index of the seedlings of the crops, there was no symptoms in spinach such as spotting and color change of leaves. EFD-1 showed much stronger inhibitory effect on the germination of tested crop seeds than PC-10 when crops were exposed continuously to tested deciers in soils. The growth and shoot and root in examined crops was relatively higher in PC-10 treatment than in EFD-1 treatment when compared to the control. The biomass decrease was found in all examined conditions of deciers. PC-10 showed 23-35% reduction of biomass whereas EFD-1 exhibited 39-84% loss in all examined crops at over 2% concentration. CONCLUSION: These results suggest that the effects of deicers used in this study by inputting into soil against growing tested crops cause the reduction of germination of seeds, growth, and biomass compared to the control.